2011
DOI: 10.1117/12.873700
|View full text |Cite
|
Sign up to set email alerts
|

Laser modification and characterization of Li-Mn-O thin film cathodes for lithium-ion batteries

Abstract: The development of future battery systems is mainly focused on powerful rechargeable lithium-ion batteries. To satisfy this demand, current studies are focused on cathodes based on nano-composite materials which lead to an increase in power density of the LIB primarily due to large electrochemically active surface areas. Electrode materials made of lithium manganese oxides (Li-Mn-O) are assumed to replace commonly used cathode materials like LiCoO 2 due to less toxicity and lower costs. Thin films in the Li-Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…The film thickness was determined with a surface profilometer (Tencor P-10) and counted 2-3.3 μm depending on the position of the substrate on the plate. The density of an as-deposited Li-Mn-O thin film with a thickness of about~67 nm was measured to be about 4 g/cm 3 via X-ray reflectivity [21] and was considered for calculation of the active mass for electrochemical cycling of laser annealed thin films assuming that no mass losses occur [30] during the annealing process at temperatures of T = 680°C.…”
Section: Thin Film Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…The film thickness was determined with a surface profilometer (Tencor P-10) and counted 2-3.3 μm depending on the position of the substrate on the plate. The density of an as-deposited Li-Mn-O thin film with a thickness of about~67 nm was measured to be about 4 g/cm 3 via X-ray reflectivity [21] and was considered for calculation of the active mass for electrochemical cycling of laser annealed thin films assuming that no mass losses occur [30] during the annealing process at temperatures of T = 680°C.…”
Section: Thin Film Depositionmentioning
confidence: 99%
“…Other in-situ studies were focused on reversible and irreversible transformations of stoichiometric LiMn 2 O 4 in air [16] or on in-situ X-ray diffraction (XRD) studies during lithium deintercalation from the spinel host structure [17]. rf magnetron sputtering is one promising method for synthesizing thin lithium manganese oxide films which have model character [18][19][20][21] and to study clearly their structural behavior due to the absence of carbon and binder as can be found in tape cast electrodes. Rapid laser annealing is one possible technique for crystallization of thin cathodes such as LiCoO 2 [22][23][24] or Li-Mn-O [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rather new application field for laser material processing is the development of 3D structures in lithium-ion batteries based on nano-scaled materials and thin films [71][72][73][74][75][76][77][78][79][80][81][82]. For this purpose, laser annealing and laser structuring of thin film electrodes made of LiCoO2, SnO2 and LiMn2O4 were recently investigated.…”
Section: La and Ls Of Thin Film Electrodesmentioning
confidence: 99%
“…Unfortunately, this approach is unfeasible for each type of electrode system, in particular for thick film electrodes [9][10][11][12][13]. Therefore, laser direct structuring of the active electrode material has been developed for thin film electrodes made of LiCoO 2 , LiMn 2 O 4 , SnO 2 or fluorine doped SnO 2 (FTO) [14][15][16][17][18][19][20][21][22][23]. In a very recent approach, it was shown that laser-structuring can be applied for LiCoO 2 , LiMn 2 O 4 , LiNi 1/3 Mn 1/3 Co 1/3 O 2 and silicon composite electrodes with film thicknesses of 50 to 100 µm [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%